ANALISIS STRATEGI OPTIMALISASI PENDAPATAN ASLI DAERAH DALAM MEWUJUDKAN KEMANDIRIAN FISKAL DI KABUPATEN PADANG PARIAMAN - Zarma Hanifah; Aldri Frinaldi; Nora Eka Putri; Asnil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Local Own Source Revenue (PAD) is a crucial component in assessing the level of fiscal independence and the ability of local governments to finance development autonomously. However, the contribution of PAD in Padang Pariaman Regency’s Revised Local Government Budget (APBD) for 2024 remains low less than ten percent of the total regional revenue indicating high fiscal dependency on central government transfers. This study aims to analyze the current condition of PAD in Padang Pariaman Regency, identify the key factors hindering its growth, and formulate relevant optimization strategies to strengthen local fiscal independence. The research employs a descriptive qualitative method through document analysis of local government regulations, Central Bureau of Statistics (BPS) reports, and recent academic literature. The findings reveal that the low PAD contribution is influenced by a narrow local tax base, low taxpayer compliance, limited capacity of financial management personnel, and unproductive asset utilization. Recommended strategies include tax and levy intensification and extensification, productive asset management, implementation of digital-based tax and levy systems, and enhancement of transparency and public participation. The consistent implementation of these strategies is expected to strengthen fiscal independence, expand fiscal space for development, and promote transparent, accountable, and sustainable local financial governance.